Cine documental y 15-M, un diálogo a múltiples voces - Laura Grifol-Isely (Cahiers de Civilisation Espagnole Contemporaine)
Starting from the documentaries El despertar de les places. Un any de 15-M (Güell & Oriola, 2012), MACBA: La dreta, l’esquerre i els rics (SUB, 2013), Ciutat Morta (Artigas & Ortega, 2013) and Informe general II. El nuevo rapto de Europa (Portabella, 2015), this paper intends to explore some productions whose emergence could hardly be understood without the essential contribution of 15-M. By adopting the concept of 15-M as a unifying factor of a previously present series of synergies, it is about showing the power of movement to catalyze impulses, and the representative role that documentary has been playing, both to channel questions and to open new political, economic and social perspectives. By assuming this role, the documentary has helped to deconstruct those anchorages of a self-satisfied democracy whose postulates, as the facts show (a huge crisis which presupposes a crisis of the Transition model), has weakened to the point of proclaiming the need to be subjected to questioning.